Autonomy support and control in weight management: What important others do and say matters - Ng, J.; Ntoumanis, Nikos; Thøgersen-Ntoumani, Cecilie (John Wiley & Sons Ltd., 2014)
Objectives. Drawing from self-determination theory (Ryan & Deci, 2002, Overview of self-determination theory: Anorganismic-dialectical perspective. In E. L. Deci&R.M. Ryan (Eds.), Handbook of self-determination research (pp. 3–33). Rochester, NY: The University of Rochester Press.), we examined how individuals’ psychological needs, motivation, and behaviours (i.e., physical activity and eating) associated with weight management could be predicted by perceptions of their important others’ supportive and controlling behaviours.Methods. Using a cross-sectional survey design, 235 participants (mean age = 27.39 years, SD = 8.96 years) completed an online questionnaire. Results. Statistical analyses showed that when important others were perceived to be more supportive, participants reported higher levels ofmore optimal forms of motivation for weight management, which in turn predicted more physical activity and healthy eating behaviours. In contrast, when important others were perceived to be controlling, participants reported higher levels of less optimal forms of motivation, which in turn predicted less physical activity and healthy eating behaviours, as well as more unhealthy eating behaviours. Significant indirect effects were also found from perceived support and control from important others to physical activity and eating behaviours, all in the expected directions. Conclusions. The findings support the importance of important others providing support and refraining from controlling behaviours in order to facilitate motivation and behaviours conducive to successful weight management.